A Drosophila melanogaster ortholog of pentatricopeptide repeat domain 3 (PTCD3) is essential for development. - Imura, E.; Enya, S.; Niwa, R. (microPublication Biology, 2023)
Mitochondrial DNA (mtDNA) replication and transcription are essential for cellular energy metabolism. It has been suggested that pentatricopeptide repeat (PPR) proteins regulate various aspects of mitochondrial RNA metabolism, including transcription, processing, maturation and stability, and protein synthesis. However, an in vivo requirement of PPR proteins in RNA metabolism has not been fully examined. In this paper, we focus on the Drosophila melanogaster homolog of PPR domain 3 (PTCD3), encoded by the CG4679 gene. A loss-of-function mutant of PTCD3 is lethal during the second instar. In addition, mutants exhibit reduced expression of a group of genes related to mitochondrial function and ribosome biogenesis, and conversely, they show up-regulated expression of neuronal development-related genes. These results suggest that PTCD3 has important functions in relation to mtDNA and is essential for development.